DETERMINANTS OF MUZAKKI’ PREFERENCE IN INDONESIA: CONCEPTUAL FRAMEWORK ANALYSIS - VIMA TISTA PUTRIANA; YURNIWATI YURNIWATI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2019)
This paper aims to critically evaluate a conceptual framework of determinants of muzakki’ preferences in Indonesia when discharging their zakat obligations developed in Putriana (2018). Understanding preferences of muzakki in Indonesia is critical due to the huge zakat potential owned by Indonesia that can be explored and utilized by zakat institutions for maximum benefits of Indonesian people. The knowledge and understanding of muzakki’ preferences in choosing their zakat distribution channels will help policy makers to issue regulations required that help zakat institutions amplifying their roles and capacity. For zakat institutions, the knowledge and understanding is useful to formulate strategies needed to persuade muzakki in Indonesia to trust them managing their zakat. This study contributes to the development of a more comprehensive conceptual framework of determinants of muzakki’ preferences in Indonesian context. The current study also attempts to establish communication among researchers with different backgrounds working on the topic of muzakki’ preferences